Construction of Ideological State Apparatus in the New Order Regime Against Communism in Indonesia - Mayrudin, Yeby Ma'asan (Faculty of Law, Universitas Negeri Semarang, 2017)
Gramsci’s hegemony theory underlies the theory of ideological state apparatus Althusser studied in this paper, essentially also a repression of power. In empirical life, to create the subjectivity of society, the power paradigm of the New Order era relies heavily on the repressive state apparatus, and the ideological state of the apparatus. The paradigm was also known as state corporatism. This paper discusses two important things related to ideological state apparatus related to communism in Indonesia, namely: (1) the interpretation of communism in the new order regime, and (2) ideological state apparatus in the new order era.